Repeated arson: data from criminal records - Barnett, Winfried; Richter, Paul; Renneberg, Babette (Forensic science international, 1999)
The criminal careers of all arsonists convicted in former West-Germany between 1983 and 1985 who were found not to be responsible due to diminished responsibility for psychiatric reasons and a random sample (every third) of all criminally liable arsonists during the same period of time were followed up until 1994 by means of their trial records. Reappearance before the court for arson did not differ between the groups. When subjects are grouped by the additional occurrence of crimes other than arson, however, arsonists with diminished responsibility are the most problematic group: In comparison with all other subgroups, the arsonists who were partly responsible who did not commit any crimes other than arson showed the highest number of fire-setting incidents. Among the arsonists who committed other crimes as well, arsonists with diminished responsibility had the highest number of additional offences.
Gesehen am 09.12.2020